Standard operating procedure and quality control standards for intravitreal injection in Guangdong Province - Group Standards Team of SOP and Quality Control Standards for Intravitreal Injection in Guangdong (Yanke Xuebao)
Intravitreal injection represents the primary method of drug administration for a range of common chronic endophthalmic diseases, including age-related macular degeneration, diabetic retinopathy and retinal vein occlusion.Recognized for its high clinical efficacy, procedural standardization, and operational accessibility, this has become a routine clinical practice in ophthalmology. In alignment with the "National Eye Health Plan during the 14th Five-Year Plan period (2021–2025)" and the patient-centered service philosophy, this approach optimizes treatment processes and enhances patient experience and therapeutic outcomes while ensuring medical safety. Furthermore, Guangdong Province is poised to become a pivotal hub for ophthalmic care within the Guangdong-Hong Kong-Macao Greater Bay Area, anticipating a growing influx of patients from Hong Kong and Macao. This necessitates the development of a unified intravitreal injection standard tailored to regional healthcare integration. Under the auspices of the Guangdong Medical Association, a consortium led by Zhongshan Ophthalmic Center, Sun Yat-sen University, and 21 collaborating medical institutions across Guangdong, formulated this standard. Through iterative reviews involving correspondence-based evaluations and multidisciplinary expert consultations, 35 distinguished specialists refined the standard,synthesizing global best practices with insights into the Greater Bay Area’s unique ophthalmological landscape. This group standard systematically outlines the basic requirements, indications and contraindications of intravitreal injection,establishes a new standard operating procedure for intravitreal injection and quality control standards for this procedure.In addition, we have introduced guidance for the clinical application of this technique and quality assessment, as well as for the prevention and management of complications or adverse reactions.